Perception of factors influencing labour turnover - Horak, James Dirk (My University, 2011)
The ongoing war for talent has resulted in many companies focussing more time and effort on retaining their employees, and understanding why they leave so that a successful retention strategy can be developed. Information technology (IT) has become a critical tool in ensuring the success and competitiveness of companies, but as many IT leaders understand, it is the people and not the systems alone that are the key factor. The context of this research is therefore to understand the perceived factors that influence the labour turnover of IT workers in South Africa. A single case study approach was used focussing on the IT developers in a single, large company operating in the financial and insurance services sector. Data was gathered from exit interviews, market information, and face to face interviews with both past and current employees. This data was evaluated against the findings of the literature review. The initial findings of the research indicated four main factors that contributed to the turnover of IT workers, these being promotions and career growth, technology and skills development, financial factors, and management and the working environment. The impact of these factors differed amongst the employees when factors such as gender, race and age were taken into account, indicating that any company focussing on retaining its employees required a deeper understanding of the reasons behind staff turnover
MBA - WBS
Keywords: Talent management; Retention of staff; Information technology